Increased dietary protein in the second trimester of gestation increases live weight gain and carcass composition in weaner calves to 6 months of age - Miguel-Pacheco, G.G.; Curtain, L.D.; Rutland, Catrin S.; Knott, L.; Norman, S.T.; Phillips, N.J.; Perry, V.E.A. (Cambridge University Press, 2017)
Genetically similar nulliparous Polled Hereford heifers from a closed pedigree herd were used to evaluate the effects of dietary protein during the first and second trimester of gestation upon fetal, placental and postnatal growth. Heifers were randomly allocated into two groups at 35d post AI (35dpc) to a single bull and fed High (15.7%CP) or Low (5.9%CP) protein in the first trimester (T1). At 90dpc, half of each nutritional treatment group changed to a High or Low protein diet for the second trimester until 180dpc (T2). High protein intake in the second trimester increased birthweight in females (P = 0.05) but there was no effect of treatment upon birthweight when taken over both sexes. Biparietal diameter was significantly increased by high protein in the second trimester with the effect being greater in the female (P = 0.02) but also significant overall (P = 0.05). Placental weight was positively correlated with birth weight, fibroblast volume, and relative blood vessel volume (P < 0.05). Placental fibroblast density was increased and trophoblast volume decreased in the high protein first trimester treatment group (P <0.05). There was a trend for placental weight to be increased by high protein in the second trimester (P = 0.06). Calves from heifers fed the high protein treatment in the second trimester weighed significantly more on all occasions preweaning (at one month (P = 0.0004), 2 mths (P = 0.006), 3 mths (P = 0.002), 4 mths (P = 0.01), 5 mths (P = 41 0.03), 6 mths (P = 0.001)), and grew at a faster rate over the 6 month period. By 6 mths of age the calves from heifers fed high nutrition in the second trimester weighed 33kg heavier than those fed the low diet in the second trimester. These results suggest that dietary protein in early pregnancy alters the development of the bovine placenta and calf growth to weaning.